Engaging in design activism and communicating cultural significance through contemporary heritage storytelling: A case study in Brisbane, Australia. Issue 3 (21st November 2016) - Wilson, Kimberley; Desha, Cheryl
Abstract : Purpose: The purpose of this paper is to discuss the role of contemporary storytelling in preserving built heritage, as a mechanism for extending the useful life of buildings. Design/methodology/approach: The authors adopted a qualitative action research approach to consider the role of storytelling. A creative, multi-method approach (i.e. a "Brisbane Art Deco" publication and associated marketing campaign) was used as a case study to explore the contours of such an approach and its efficacy in engaging the community. Findings: This paper highlights the potential of contemporary approaches to heritage storytelling, including utilising digital technologies, to engage a diverse range of people that may not have otherwise participated. The authors propose the value of taking a creative and whole-of-society approach – such as that used in this case study – to heritage storytelling. Research limitations/implications: The case study discussed provides a phenomenological insight into one version of "contemporary heritage storytelling". The findings have immediate implications for prioritising research into storytelling for the preservation of built heritage. Practical implications: The case study demonstrates opportunities for community engagement through storytelling and highlights potential strategies to effectively contribute to a greater societal value of cultural heritage. Originality/value: This research contributes to theory and practice around the management of cultural heritage, and highlights the usefulness of employing such a strategy to reach and engage a broader audience.